White-collar crime and stock nexus: empirical study from announcement effect - Liew, Samuel Wei Siew (Universiti Malaysia Sarawak, (UNIMAS), 2011)
White-collar crime victimization has been found in many studies to be more serious than conventional crime. The financial loses incurred can never be quantified with certainty. Victims of the crime are often stigmatized for a long period of time. The existence of white-collar crime can cause much damage to the reputation of the companies in Malaysia and hurt the image of the country as a whole. Recent survey reports and statistics suggest that the number of crime is still growing and it cannot be left unchecked A share price event study confirms a negative announcement effect of white-collar crime in Malaysia. Negative abnormal performance is found after the day of announcement fOJ 10 continuous trading days. The stock market in Malaysia is thus concluded to be inefficient. Other findings concern the causes, indicators, discovery, and regulations of white-collar crime. Opportunistic causes are perceived to be the most common causes of the crime in Malaysia, whereas the most apparent indicators relate to the behavior of an individual. Internal controls are then found to be very important in detecting and preventing white-collar crime in a company. The research paper also finds education to be an effective element in regulating white-collar crime in Malaysia. The stock market, albeit not efficient, appears to have the power to discipline unethical companies when shareholders dispose their stocks. It is hoped that companies will be deterred from engaging in illegal conducts. The other findings aim to increase stakeholders' awareness towards the facts and implications of white-collar crime in Malaysia. It is imperative for every potential and existing investor to have some basic understanding of white-coUar crime before they are able to fight the crime in Malaysia.